Social Effects of Fractures of the Neck of the Femur. Issue 5928 (17th August 1974) - Thomas, T. Glyn; Stevens, R. S.
Abstract : One-hundred-and-five patients were visited at home one year or more after they had been treated for proximal femoral fractures to assess the extent to which their social independence had been affected by the incident. Since the accident 25% had become more dependent. The principal factors contributing to this outcome included established dependence, great age at the time of injury, and a poor clinical result. The implications for social services and community care of preventing social impairment justify a more comprehensive investigation. The need for close co-operation between orthopaedic surgeons and geriatricians, already widely acknowledged, is further emphasized.